Histophilus somni myocarditis and leptomeningitis in feedlot cattle: case report and occurrence in South America - Margineda, Carlos Augusto; O'Toole, Donal; Prieto, Mónica; Uzal, Francisco A.; Zielinski, Gustavo Carlos (SAGE Publishing, 2020)
We investigated deaths in a group of feedlot steers in Argentina. The main findings in 3 steers autopsied were pulmonary congestion and edema, necrotizing myocarditis, pericarditis, suppurative leptomeningitis, and bronchopneumonia. Histophilus somni was detected by bacterial culture and immunohistochemistry in the hearts of the 3 animals. Partial sequences of the 16S rRNA gene of a H. somni isolate had 99% similarity with other H. somni sequences in GenBank. Most reports of H. somni septicemia in cattle originate from North America and western Europe. There is scant information about cardiac histophilosis in South America. A survey of diagnostic laboratory personnel in 7 South American countries documented various forms of bovine histophilosis in Argentina, Brazil, Uruguay, and Venezuela.